Knockdown of Kinase Family 15 Inhibits Cancer Cell Proliferation In vitro and its Clinical Relevance in Triple-Negative Breast Cancer - Sheng, Jiayu; Xue, Xiaohong; Jiang, Ke (Current Molecular Medicine, 2019)
Purpose: Breast cancer is the most prevalent malignancy and the leading cause of death among women. Triple-negative breast cancer (TNBC) is a subtype of breast cancer and shows a distinctly aggressive nature with higher rates of relapse and shorter overall survival in the metastatic setting compared to other subtypes of breast cancer. This study aimed to assess the effect of KIF15 on various clinicopathological characteristics, survival analysis, and cell proliferation in triple-negative breast cancer, which has not been reported to our knowledge. Methods: A total of 165 patients with triple-negative breast cancer were enrolled and clinical data were obtained, Mann-Whitney U analysis was performed to assess the correlation between the expression of KIF15 and clinical pathological characteristics of TNBC patients. Survival analysis was performed by Kaplan-Meier analysis and Log-rank test. The expression levels of KIF15 in cancer tissues and adjacent tissues were evaluated via Sign test. Lentivirus was used to down-regulate the expression of KIF15 in TNBC cells. The cell proliferation, colony formation capacity and apoptosis were examined by MTT, Giemsa staining and flow cytometry assay, respectively. Results: Our results showed that, among the 165 TNBC patients, the expression of KIF15 was positive correlation with clinicopathological features of TNBC. In addition, KIF15 low-expression group showed higher disease-free survival than KIF15 highexpression group and univariate analysis showed that KIF15 high-expression group appeared higher mortality than KIF low-expression group (P ≤ 0.05). Meanwhile, the expression levels of KIF15 in cancer tissue notably up-regulated in comparison with adjacent tissue. In vitro, knockdown of KIF15 significantly promoted cell apoptosis and suppressed cell proliferation and colony formation of TNBC cells. Conclusion: By utilizing survival analysis, we found that high-expression of KIF15 in the TNBC samples were associated with poorer overall survival, while the anti-tumor effect of KIF15 knockdown was also confirmed at the cellular level in vitro. Taken together, KIF15 can be applied as a potential diagnostic and therapeutic target in TNBC.
Keywords: KIF15